2012
DOI: 10.3109/03009742.2011.630328
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence ofPneumocystis jiroveciicolonization among patients with autoimmune inflammatory diseases and corticosteroid therapy

Abstract: Patients with AID, especially those over 60 years of age, display a high prevalence of colonization with P. jirovecii. Clinicians should be aware of this and ensure that they consider the possibility of PCP when pulmonary symptoms arise in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
3
15
2
4
Order By: Relevance
“…Bu hastaların dosyaları incelendiğinde; böbrek tx sonrası pnömoni gelişen iki hasta ile RA ve BDH tanılı hastaların ampirik anti-PCP tedavisine yanıt verdikleri, tedavi İmmün sistemi baskılanmış hastalarda gözlenen P.jirovecii varlığının, immün sistemi sağlam kişilere oranla daha fazla olduğu bilinmektedir 1,2,8 . Kortikosteroid kullanımı en önemli risk faktörleri arasında gösterilmekle birlikte, yeni nesil immünomodülatör ilaçların kullanıma girmesiyle, özellikle hematolojik malignitelerde, organ transplant alıcılarında, infl amatuvar bağ dokusu hastalıklarında yüksek P.jirovecii pozitifl ikleri bildirilmiştir [3][4][5]9,11 . Bu çalışmada da, immünosüpresif 65 hastanın 26 (%40)'sında nPCR ile pozitifl ik saptanır-ken, bu oran immünokompetan hastalarda %18.5 (5/27) olarak bulunmuştur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bu hastaların dosyaları incelendiğinde; böbrek tx sonrası pnömoni gelişen iki hasta ile RA ve BDH tanılı hastaların ampirik anti-PCP tedavisine yanıt verdikleri, tedavi İmmün sistemi baskılanmış hastalarda gözlenen P.jirovecii varlığının, immün sistemi sağlam kişilere oranla daha fazla olduğu bilinmektedir 1,2,8 . Kortikosteroid kullanımı en önemli risk faktörleri arasında gösterilmekle birlikte, yeni nesil immünomodülatör ilaçların kullanıma girmesiyle, özellikle hematolojik malignitelerde, organ transplant alıcılarında, infl amatuvar bağ dokusu hastalıklarında yüksek P.jirovecii pozitifl ikleri bildirilmiştir [3][4][5]9,11 . Bu çalışmada da, immünosüpresif 65 hastanın 26 (%40)'sında nPCR ile pozitifl ik saptanır-ken, bu oran immünokompetan hastalarda %18.5 (5/27) olarak bulunmuştur.…”
Section: Discussionunclassified
“…Ancak klinik örneklerde P.jirovecii'nin veya DNA'sının saptanması mutlaka enfeksiyon anlamına gelmemektedir. Klinik olarak semptom vermeyen kişilerde, organizmanın veya DNA'sının tespit edilmesi kolonizasyon olarak tanımlanmıştır 7,9 . Bu nedenle mikroskopisi negatif, ancak PCR pozitif bulunan hastalarda enfeksiyonun tanısı ve tedavisi için klinik değerlendirme oldukça önemlidir.…”
Section: Introductionunclassified
“…PJ colonization has been detected in 16-29 % of patients with a variety of systemic autoimmune diseases [16,17] and Mori et al identified a cluster of de novo PCP infections in RA patients from a single outpatient clinic over a 2-year period [18]. Risk factors for PJ colonization include age over 60, chronic pulmonary disease, smoking, low absolute lymphocytes and CD4 cells count, low serum immunoglobulins levels, use of corticosteroids (both its recent administration and daily dose of prednisolone over 15 mg) and methotrexate [16,17]. Even though none of these risk factors appear specific [16], age was the strongest contributor [17].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for PJ colonization include age over 60, chronic pulmonary disease, smoking, low absolute lymphocytes and CD4 cells count, low serum immunoglobulins levels, use of corticosteroids (both its recent administration and daily dose of prednisolone over 15 mg) and methotrexate [16,17]. Even though none of these risk factors appear specific [16], age was the strongest contributor [17]. In a study by Mekinian et al, none of the patients with a systemic autoimmune disease and PJ colonization disease developed PCP, possibly due to the rapid decrease of the corticosteroid dose [16].…”
Section: Discussionmentioning
confidence: 99%
“…Pneumocystis jiroveci (PJ) colonisation is increased in patients with autoimmune diseases (AID) (29 %) compared with healthy control (3 %) [1]. However PJ pneumonia (PCP) is uncommon and often fatal in patients with AID [2].…”
mentioning
confidence: 99%